Low-level amikacin resistance induced by AAC(6′)-Ib and AAC(6′)-Ib-cr in extended-spectrum β-lactamase (ESBL)-producing Enterobacterales isolated from urine in children - Hassan Al, Mana (2021)
Amikacin is commonly used in children in combination with other agents as a last-resort treatment for severe infections caused by multidrug-resistant Gram-negative bacteria. Amikacin is also prescribed empirically in febrile neutropenia in children with cancer and in acute pulmonary exacerbations in cystic fibrosis patients. Over the past few years, however, amikacin has been increasingly used to treat urinary tract infections (UTIs) in children caused by Enterobacterales producing extended-spectrum β-lactamases (ESBLs), given the low resistance rates to this agent among ESBL-producing uropathogens worldwide. Resistance to amikacin in Enterobacterales can be caused by multiple mechanisms, including 16S rRNA methyltransferases. However, the most common cause is the aminoglycoside N-acetyltransferase AAC(6′)-Ib, which acetylates amikacin, tobramycin, kanamycin and netilmicin but spares gentamicin, while its bifunctional variant AAC(6′)-Ib-cr also modifies ciprofloxacin and norfloxacin . AAC(6′)-Ib-cr is frequently co-produced by CTX-M-type ESBL-producing isolates, particularly CTX-M-15, conferring low-level resistance to amikacin with minimum inhibitory concentrations (MICs) that do not exceed susceptible breakpoints. The study found that isolates carrying AAC(6′)-Ib-cr have on average a 2-fold higher amikacin MIC. The increased MIC may impact the ability to achieve a Cpeak/MIC > 8 assuming hypothetical peak concentrations between 20 mg/L and 30 mg/L, which could impact the antibiotic's efficacy as a theraputic agent.